(untitled) (Revista Brasileira de Computação Aplicada, 2015)
This paper presents a computer method to find the best sine-based function, in the sense of least squares, to fit periodic data. Even though the least squares method is not a novelty, there is a void in the literature about its use to find trigonometric functions, particularly when it gives rise to nonlinear systems, as it is done in this article. The respective code, implemented in the Matlab programming language, is detailed and analyzed exploring experimental data from the air and soil temperatures measured along the year in earth air heat exchangers (EAHE) built in the facilities of a case study house in the Brazilian state of Rio Grande do Sul. The fitting curves have been employed by the authors in different works to define boundary conditions to study new computer models of EAHE.